2018
DOI: 10.1177/1479972318809456
|View full text |Cite
|
Sign up to set email alerts
|

Pain in patients with chronic obstructive pulmonary disease indicated for post-acute pulmonary rehabilitation

Abstract: Pain is a significant problem in stable chronic obstructive pulmonary disease (COPD) and is associated with other symptoms, worse health status and lower functional status. Not much is known about pain in unstable disease. The primary aim of the present study is to investigate prevalence, characteristics and relationships of pain in patients with COPD hospitalized for an acute exacerbation (AECOPD) and indicated for post-acute pulmonary rehabilitation (PR). This cross-sectional observational study included 149… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 39 publications
1
25
0
1
Order By: Relevance
“…The apparent paradoxical relationship between pain and lung function was also reported in lots of pain studies in COPD studies (12,39,40). This inverse relationship, probably also caused by selection bias, also can be interpreted that other symptoms like dyspnea were more distressing than pain, leading to more focus on dyspnea and less on pain, also causing patients to be reluctant to spontaneously report pain (41)(42)(43).…”
Section: Discussionmentioning
confidence: 80%
“…The apparent paradoxical relationship between pain and lung function was also reported in lots of pain studies in COPD studies (12,39,40). This inverse relationship, probably also caused by selection bias, also can be interpreted that other symptoms like dyspnea were more distressing than pain, leading to more focus on dyspnea and less on pain, also causing patients to be reluctant to spontaneously report pain (41)(42)(43).…”
Section: Discussionmentioning
confidence: 80%
“…Random sampling did not occur in any studies and all studies were identified as being at high risk of non-response bias, as no information was provided about potential participants who were approached for inclusion but did not participate. One study 27 was classed as low risk of bias with regard to the instruments used, as it applied valid and reliable instruments.…”
Section: Resultsmentioning
confidence: 99%
“…By 2016, there were 26 papers available as a potential evidence base to the 30 CPGs published between 2010–2015 [46,47,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,92,93,94,95,96,97,98,99,100,101,102]. Across 2017 to 2018, at least another nine studies have been published providing estimates of pain prevalence in people with COPD, which would be available to developers of future CPGs or of CPGs currently underway or being updated [6,19,20,26,31,32,33,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In people with chronic obstructive pulmonary disease (COPD), persistent pain is a common clinical issue adversely impacting daily function, symptom burden, and quality of life [1,2,3]. To date, there are at least 34 studies [1,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36] and two systematic reviews [2,3] available that report direct estimates of pain prevalence in people with COPD (Figure 1). Prevalence rates for pain vary markedly and range between 21 to 82% (Figure 1) with a mean pooled estimate of 66% (95% Confidence Interval (CI) 44–85%) [2].…”
Section: Introductionmentioning
confidence: 99%